The Impact of Seasonality on Air Quality in Terms of Pollution with Substances Hazardous to the Environment - Małgorzata Kida; Sabina Ziembowicz (Applied Sciences)
The study presents an analysis of the concentrations of polycyclic aromatic hydrocarbons (PAHs) and particulate matter with a diameter of less than 10 µm (PM10) in the air across various locations, as well as their impact on human health. Research in this area was conducted at eight stations as part of the national environmental monitoring system run in Poland by the Chief Inspectorate for Environmental Protection. Daily measurement data of PM10 and the concentrations of PAHs associated with these particles were analyzed for the period from January to December 2023. The results showed that pollutant concentrations in the atmosphere vary depending on location, season, and meteorological conditions. The highest concentrations were observed during the winter season, when the combustion of solid fuels increases, while the lowest concentrations were recorded in the summer. The total concentration of PAHs ranged from 0.35 to 34.50 ng/m3. The annual average concentration of PM10 at the analyzed stations was 19.29 ± 3.01 µg/m3. Principal component analysis indicated that PAHs in the air primarily originate from emissions related to transportation, biomass combustion, and industry. Furthermore, the estimated health risk, considering the Incremental Lifetime Cancer Risk (ILCR) index, showed that the risk of cancer associated with inhaling PAHs by children and adults did not exceed the permissible limits. The main contributor to the total carcinogenic activity of the PAH mixture was benzo(b)fluorantene (BbF) (31.5%), followed by benzo(a)pyrene (BaP) (5.5%), indeno(1,2,3-cd)pyrene (IP) (18.2%), benzo(j)fluorantene (BjF) (12.9%), benzo(k)fluorantene (BkF) (8.5%), benzo(a)anthracene (BaA) (2.5%), and dibenzo(a,h)anthracene (DBahA) (1.0%).